2017
DOI: 10.1590/2317-1782/20172015217
|View full text |Cite
|
Sign up to set email alerts
|

Recursos comunicativos de executivos e profissionais em função operacional

Abstract: RESUMO Objetivo Analisar os relatos de uso de recursos comunicativos por executivos no ambiente corporativo e compará-los com os recursos de profissionais em função operacional. Método Participaram 82 profissionais voluntários, sendo 50 em funções executivas (GE) e 32 colaboradores em funções operacionais (GO), do setor industrial de Caxias do Sul e região. Para a pesquisa, foi aplicado um protocolo com 4 aspectos: dados pessoais, autoavaliação do comportamento comunicativo, autoavaliação de recursos comunic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
6
0
3
Order By: Relevance
“…In the results of our study, we observed that expressing fear of speaking in public did not depend directly on a positive or negative self-assessment when speaking in public (SSPS). Authors often argue that good communicators may not be able to get rid of the fear of speaking altogether, since the basis of fear is physiological and mutifactorial (17,18) .This data is relevant so that communicative assessments value coping strategies to minimize fear including strategies for self-knowledge (14,(19)(20)(21) , organization and domain of speech, public speaking experiences (14) , or therapeutic techniques utilizing breathing exercises and the voice (10,16,20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the results of our study, we observed that expressing fear of speaking in public did not depend directly on a positive or negative self-assessment when speaking in public (SSPS). Authors often argue that good communicators may not be able to get rid of the fear of speaking altogether, since the basis of fear is physiological and mutifactorial (17,18) .This data is relevant so that communicative assessments value coping strategies to minimize fear including strategies for self-knowledge (14,(19)(20)(21) , organization and domain of speech, public speaking experiences (14) , or therapeutic techniques utilizing breathing exercises and the voice (10,16,20) .…”
Section: Discussionmentioning
confidence: 99%
“…The total score is obtained by summating the ten items of the protocol. The negative subscale score should be inverted (14) . The minimum score was 0 points to the maximum score of 50 points.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the communicative resources, an online version of the self-assessment of communicative behavior protocol was created. This protocol was previously developed in a study that analyzed the communication resources of managers and business professionals (7) . This protocol was divided into three parts: 1) personal data; 2) self-assessment of vocal behavior and communicative resources; 3) identification of resources with a negative and positive influence on their own communicative discourse.…”
Section: Methodsmentioning
confidence: 99%
“…The first part of the protocol (7) had items of personal data including name, age, sex, years of professional experience, professional position, schooling, company that the person represented and professional registration number; these data was included to the protocol version of the present study. The second part counted with 14 questions of the self-assessment of vocal behavior and use of communicative resources related to their communication in professional and personal environments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation